Dokumentarische Schulforschung Schwerpunkte: Schulentwicklung - Schulkultur - Schule als Organisation - Hinzke, Jan-Hendrik; Bauer, Tobias; Damm, Alexandra; Kowalski, Marlene; Matthes, Dominique (Dokumentarische Schulforschung, 2023)
Documentary school research establishes a research direction in which the interrelationship of subject-related knowledge acquisition and methodological-methodological aspects is reflexively examined. This volume is the prelude to several anthologies that have been produced in theDFG-funded network ""Documentary School Research"" (NeDoS) and are dedicated to this interrelationship. Three subject areas of documentary school research are the focus of this first volume: School Development, School Culture and School as Organisation. Fundamental questions are raised and dealt with in conceptual contributions. The current research situation is systematically presented in study reviews for each of the three subject areas as well as for existing English-language studies. Current approaches and results of school research operating with the documentary method are also presented in empirical contributions. Finally, the anthology also shows gaps and desiderata in school research using the documentary method and encourages further work in this field of research.